Study of thermal, structural, microstructural, vibrational and elastic properties of MnxMg0.8–xZn0.2Fe2O4 (0.1 ≤ x≤ 0.7) ferrite nanoparticles. Issue 12 (15th June 2023) - Prasad, S.A.V.; Srinivas, Ch.; Jeevan Kumar, R.; Ranjith Kumar, E.; Vijaya Babu, K.; Meena, Sher Singh; Bhatt, Pramod; Yusuf, S.M.; Sastry, D.L.
Abstract: Sol-gel auto combustion method has been used to synthesize a series of Mn x Mg0.8– x Zn0.2 Fe2 O4 (0≤ x ≤ 0.7 at a step of 0.1) nano ferrites. Thermogravimetric and Differential scanning calorimetry (TGA and DSC) studies revealed that the weight loss changes happened up to the temperature 700 °C. A stable ferrite phase without weight loss was found above 750 °C. XRD patterns gave the confirmation of cubic spinel phase of ferrite samples along with the minor amounts of α -Fe2 O3 phase. The α -Fe2 O3 phase appears to be increasing in the ferrite compositions for x ≥ 0.4. The experimental lattice parameter ( a ) and average crystallite size (< D >) are found to be in the range of 8.4205–8.4479 Å and 34.9–54.7 nm. A systematic variation was not found in both a and < D > with the substitution of Mn 2+ . FE-SEM micrographs do not provide individual particle sizes, but their nature showed the agglomeration of ferrite nanoparticles with magnetic interactions. The obtained higher and lower vibrational bands ( υ 1 and υ 2 ) in FTIR spectra confirm spinel phase in support of XRD analysis. The ratio of bulk modulus to rigidity modulus ( B / R ) is greater than 1.75 for all ferrite compositions showing that the mechanical behaviour is ductile. The value of Poisson ratio ( σ = 0.26) revealed the isotropic nature of ferrite compositions. Different parameters like cation distribution, substitution of Mn 2+, configurational entropy, secondary phases and bond lengths are predominantly influencing the structural, vibrational and elastic properties of present ferrite compositions.